Futility, benefit, and transcatheter aortic valve replacement - Lindman, Brian R; Alexander, Karen P; O'Gara, Patrick T; Afilalo, Jonathan (JACC. Cardiovascular interventions, 2014)
Transcatheter aortic valve replacement (TAVR) is a transformative innovation that provides treatment for high or prohibitive surgical risk patients with symptomatic severe aortic stenosis who either were previously not referred for or were denied operative intervention. Trials have demonstrated improvements in survival and symptoms after TAVR versus medical therapy; however, there remains a sizable group of patients who die or lack improvement in quality of life soon after TAVR. This raises important questions about the need to identify and acknowledge the possibility of futility in some patients considered for TAVR. In this very elderly population, a number of factors in addition to traditional risk stratification need to be considered including multimorbidity, disability, frailty, and cognition in order to assess the anticipated benefit of TAVR. Consideration by a multidisciplinary heart valve team with broad areas of expertise is critical for assessing likely benefit from TAVR. Moreover, these complicated decisions should take place with clear communication around desired health outcomes on behalf of the patient and provider. The decision that treatment with TAVR is futile should include alternative plans to optimize the patient's health state or, in some cases, discussions related to end-of-life care. We review issues to be considered when making and communicating these difficult decisions.